2011
DOI: 10.1111/j.1445-2197.2010.05635.x
|View full text |Cite
|
Sign up to set email alerts
|

Profile, transport and outcomes of severe burns patients within an inclusive, regionalized trauma system

Abstract: Background:Severe burns represent a challenging and complex clinical presentation, requiring highly specialized burns centres that are staffed and equipped appropriately. The integration of burns care into trauma systems has been recommended. This study describes the profile, transfer and outcomes of severe burns within an inclusive, regionalized trauma system. Methods: A retrospective analysis of prospectively collected data from the Victorian State Trauma Registry for the period July 2001-June 2009 was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Victoria has a regionalised, hierarchical trauma system, which ensures transfer of patients with severe burns to the specialist service. Previous research has shown that 98% of adult patients with severe burn injury are managed at the VABS [ 13 ]. In addition, many patients with less severe burns are cared for in this service.…”
Section: Methodsmentioning
confidence: 99%
“…Victoria has a regionalised, hierarchical trauma system, which ensures transfer of patients with severe burns to the specialist service. Previous research has shown that 98% of adult patients with severe burn injury are managed at the VABS [ 13 ]. In addition, many patients with less severe burns are cared for in this service.…”
Section: Methodsmentioning
confidence: 99%
“…Victoria operates an inclusive trauma system to ensure that injured patients receive their care at the most appropriate level in the system. Previous research has shown that 98% of adult patients with severe burn injury are managed at the Victorian Adult Burns Service (VABS) housed in the Alfred Hospital in Melbourne [4].…”
Section: Settingmentioning
confidence: 99%
“…Severe burns are complex injuries with a high risk of mortality and long-term morbidity, and require management in a specialist service [1,2], where they contribute disproportionately and unpredictably to costs [3]. The Australian state of Victoria has one specialist adult burns service based at the Alfred Hospital in Melbourne which treats virtually all Victorian adult patients with severe burns [4]. Hospital funding in the state is largely determined using an activity-based case-mix approach which is designed to provide a 'rolled-up' average price for each admission, based on standardised coding [5].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with major burn injuries or those with concomitant burn injuries in addition to physical trauma should be triaged to major trauma centres with burns services. 40 The benefits of such triage are towards goal-directed resuscitation of burns shock through accurate fluid resuscitation and also the capacity for early debridement of burns injury. Blast injuries may further complicate resuscitation of such patients and clinical features of such injuries should be sought early through history and investigations.…”
Section: Trauma Reception and Resuscitationmentioning
confidence: 99%